Modernisasi Manajemen Bank Sampah Melalui Pemanfaatan Aplikasi Bank Sampah IT Mobile Pada Komunitas Bank Sampah TPI BISA Kelurahan Pagak Kecamatan Beji Kab. Pasuruan - Muhammad Imron Rosadi; Faris; Zainul Ahwan; Mulyono Wibisono (LPPM Universitas Yudharta Pasuruan, 2019)
The garbage problem in Pasuruan district has been in the emergency. This condition is caused because of garbage governance in Pasuruan Regency still use conventional method 3P (collection, transport and disposal) so that it can not reduce the amount of garbage dumped to TPA considering there is no process Waste processing done. Seeing the question of the Pasuruan district government made a waste handling policy through the SDSB Program (one village waste Bank). The Government's policy was responded well by the housewives at Taman Permata Indah Village of Pagak district of Beji District in Pasuruan Regency by forming the waste bank community TPI BISA. The establishment of waste bank TPI BISA this part of the response to the government policy while seeing the problem of many unhandled garbage that affects health and hygiene of the environment as a result of the increasing Population in the area. Household waste deposits generated within 1 month less than 6 quintals and every tendency month is increasing. Waste bank TPI BISA one of the waste bank that is sufficient to exist and has succeeded in managing the environment through the management of both organic and inorganic waste. In addition, the community also conducts garbage processing in the form of interesting and unique handcraft. But on the other hand, from the success also still leave a serious problem that the management system of waste bank TPI BISA be done by manual model so that there is often an error in recording the deposit amount Garbage whose edges often make a conflict in internal management of trash banks with members or customers of trash banks. Therefore, modernization of IT-based administrative management becomes a real need needed by waste bank TPI BISA, So that waste bank TPI BISA be worthy of an example of trash bank with IT-based management of mobile that can be developed thoroughly in Pasuruan Regency.